Role of health care workers in the care and support of women living with HIV/AIDS experiencing intimate partner violence: the case of women attending care and treatment clinic in Singida region, Tanzania - Kosia, Agnes L.; Nyamhanga, Tumaini; Frumence, Gasto; Kakoko, Deodatus; Semakafu, Ave Maria (International Journal Of Community Medicine And Public Health, 2021)
Background: Intimate partner violence (IPV) is behaviour within intimate relationship that causes physical, sexual and psychological harm. Health care workers (HCW) have a big role to play for women living with HIV/AIDS (LWHA) who are experiencing IPV. The understanding and perception of IPV towards health care workers is very important in the provision of integrated holistic care. Methods: This was a qualitative study where data was collected through in-depth interviews and focus group discussions for 24 HCW, working at a care and treatment clinic and prevention of mother to child transmission of HIV/AIDS. Content analysis was used to analyse the data. Results: The study findings showed that HCW had their own meaning and understanding of IPV that was when a male partner does something wrong to his female partner which was associated with beating, use of abusive language and refusal to provide basic needs. HCW had various roles in caring and supporting women LWHA experiencing IPV. They provided emergency medical services, health education which helped them to cope with their HIV/AIDS disease, counselled on the importance of adhering to their antiretroviral treatment medications and referral services which helped them to address their IPV as women LWHA. Conclusions: The study concluded that HCW had a very important role to play in care and support of women LWHA. They needed more training on IPV so that they will be able to provide care and support to all women living with HIV/AIDS experiencing IPV and the community at large.